Clinical Course of Factor VIII Inhibitors Developed after Exposure to a Pasteurised Dutch Concentrate Compared to Classic Inhibitors in Hemophilia A - Mauser-Bunschoten, E P; Rosendaal, F R; Nieuwenhuis, H K; Roosendaal, G; Briëf, E; van den Berg, H M (Thrombosis and Haemostasis, 1994)
After the introduction of a new pasteurised factor VIII concentrate (Factor VIII CPS-P) in The Netherlands in June 1990, an increase in the occurrence of inhibitors in hemophilia A patients was reported. The clinical course of this group of inhibitors (n = 12) was compared with hemophilia patients in whom an inhibitor developed before June 1990 (classic inhibitors) (n = 32). Striking differences were found between both groups not only in patient age (median 22 years versus 8 years) and number of exposure days (<50 − >1000 versus <50), as described in previous reports, but also in clinical course and response to treatment. In the recent group of inhibitors antibody titers showed a rapid decline when product was changed which was not the case in the group with classic inhibitors. In the group of classic inhibitors immune tolerance therapy with low dose factor VIII succeeded in 83%. Success was to a high degree dependent on the inhibitor level. In the group of recent inhibitors immune tolerance with the same concentrate was only successful in a single patient. However, once the patients were switched to another concentrate, antibody levels dropped to less than 2 BU/ml within 8 months in all patients.It seems likely that in this group of product associated inhibitors, treatment success was due to elimination of antigen stimulation rather than induction of immune tolerance.